2020
DOI: 10.1038/s41419-020-03162-w
|View full text |Cite
|
Sign up to set email alerts
|

PDK4 promotes vascular calcification by interfering with autophagic activity and metabolic reprogramming

Abstract: Pyruvate dehydrogenase kinase 4 (PDK4) is an important mitochondrial matrix enzyme in cellular energy regulation. Previous studies suggested that PDK4 is increased in the calcified vessels of patients with atherosclerosis and is closely associated with mitochondrial function, but the precise regulatory mechanisms remain largely unknown. This study aims to investigate the role of PDK4 in vascular calcification and the molecular mechanisms involved. Using a variety of complementary techniques, we found impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…Tumor cells undergo metabolic alteration to ful ll the bioenergetic and biosynthetic needs for rapid cell proliferation 45 . As an important mitochondrial matrix enzyme for cellular energy regulation 50 , PDK4 inhibits the entry of pyruvate into the TCA cycle, thus switching energy derivation to cytoplasmic glycolysis rather than mitochondrial OXPHOS 43,51 . Recently, DLBCL has been identi ed as a type of metabolic heterogeneity disease 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cells undergo metabolic alteration to ful ll the bioenergetic and biosynthetic needs for rapid cell proliferation 45 . As an important mitochondrial matrix enzyme for cellular energy regulation 50 , PDK4 inhibits the entry of pyruvate into the TCA cycle, thus switching energy derivation to cytoplasmic glycolysis rather than mitochondrial OXPHOS 43,51 . Recently, DLBCL has been identi ed as a type of metabolic heterogeneity disease 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of speci c modulator for PDK4, dichloroacetate (DCA), as a speci c inhibitor of PDK4 42,43 , was used to assess the impact of pharmacological PDK4 inhibition. Compared with rituximab alone, a signi cant increase of apoptosis was observed in cell lines when they were treated with rituximab (50 μg/mL) and DCA (5 mmol/L) for 48 hours (OCI-ly7: 20.25% ± 2.14% vs. 35.65% ± 3.87%, P = 0.0038; OCI-ly8: 13.63% ± 2.12% vs. 30.55% ± 3.39%, P = 0.0018), which is the case even in the U2932 cell line initially showing poor response to rituximab (5.54% ± 1.93% vs. 25.14% ± 3.66%, P = 0.0012; Fig.…”
Section: Targeting Pdk4 Increases Rituximab Sensitivity Against Dlbcl Cellsmentioning
confidence: 99%
“…As discussed above, this metabolic shift is seen in both the calcified vessels of atherosclerotic patients (Lee et al, 2015 ) and calcified transdifferentiated VSMCs cultured under high Pi conditions (Rashdan et al, 2020 ). Recently, it has been demonstrated that PDK4 drives the metabolic reprogramming of VSMCs toward a high rate of glycolysis followed by lactic acid generation in the cytosol (Ma et al, 2020 ). Inhibition of PDK4 abrogates VSMCs calcification by inducing lysosomal function and autophagy (Ma et al, 2020 ).…”
Section: Mitochondrial Quality Control In Vascular Calcificationmentioning
confidence: 99%
“…Recently, it has been demonstrated that PDK4 drives the metabolic reprogramming of VSMCs toward a high rate of glycolysis followed by lactic acid generation in the cytosol (Ma et al, 2020 ). Inhibition of PDK4 abrogates VSMCs calcification by inducing lysosomal function and autophagy (Ma et al, 2020 ). In conclusion, enhancing autophagy in vascular calcification pathologies may have a multitude of additional effects including inhibiting the Warburg effect, suppressing saturated fatty acid–induced vascular calcification and aiding cellular survival by clearing away the damaged mitochondria via mitophagy.…”
Section: Mitochondrial Quality Control In Vascular Calcificationmentioning
confidence: 99%
“…Although this process is traditionally considered passive, degenerative, and quiescent, recent studies suggested that VC is an active process beginning with the deposition of cell-derived matrix vesicles into the extracellular matrix, where osteogenic differentiation plays a predominant role [ 4 6 ]. Ectopic osteogenesis driven by oxidative stress and metabolic are responsible for VC initiation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%